RETHINKING THE ROLE OF KIAI LEADERSHIP IN MODERNIZING PESANTREN IN CIANJUR, WEST JAVA - Hasyim, Abdul Wahid (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This article seeks the role of the Kiai in the modernization of pesantren in Cianjur, West Java. Taking the cases of Pesantren al-Musyarrofah, Pesantren Darul Falah, Pesantren as-Syuja’i, and Pesantren Darussuada al-Amin, this research uses qualitative methods. The study found that although these Pesantrens played a significant role in da’wah, education, and the development of socio-religious institutions in Cianjur, their existence of experienced ups and downs due to the management system practiced by the pesantren leadership. In addition, it was also implied that modern management combined with the Kiai charisma has become a success factor in the modernization of the pesantren.Keywords: Islamic education, pesantren, kiai, management, leadership